Tempeh consumption patterns in Indonesian family and contribution nutritional adequacy - Trina Astuti; Marudut Sitompul; Amirah Faadhilanisyah (AcTion: Aceh Nutrition Journal, 2023)
Tempe is one of the original Indonesian traditional foods since the 16th century consumed as a snack, side dish, and vegetable. This research aimed to study consumption patterns, perceptions, and the contribution of tempeh nutrients to protein adequacy in Indonesian society. The study design is a cross-sectional study conducted online in October 2022 with 387 subjects from 34 provinces, taken purposively. Data was collected through online questionnaires. Tempe consumption data was analyzed using TKPI and compared with the RDA 2019. Data on characteristics, consumption patterns, and perceptions about tempeh are presented descriptively. Results, the average number of family members who consume tempeh is 4,3 ± 1,04 (minimum three and maximum 8) people, the frequency of consumption of tempe is 4,1 ± 1,7 times/week, the type of soybean tempeh (87,5%) with fried preparations (35%) and tempeh or crushed chili sauce (20,0%). The large portion of one meal is 50 grams. The average individual consumption is 41,75 ± 27,22 grams/capita/day. The eastern region is lower than the western and central regions. Consumption of tempeh contributes to the adequacy of protein by 10,27% - 14,6% and 30,25% to the adequacy of vitamin B12. 86,5% of subjects stated that tempeh was beneficial for heart health, anti-cancer, and antioxidants, but 14,5% of subjects stated that tempeh could increase uric acid and cholesterol, thyroid disorders, and allergies. The conclusion is that the average daily consumption of tempeh contributes one-sixth to the adequacy of protein and one-third to the adequacy of vitamin B12.